The Comprehensive Systematic Review of Vasoactive-Inotropic Score as a Predictor of Outcome in Pediatric Critical Care - Mohamad Fadli; Raka Jati Prasetya; Mutia Juliana (International Medical Journal Corp. Ltd, 2026)
Introduction: The Vasoactive-Inotropic Score (VIS) quantifies cardiovascular support in critically ill children by aggregating vasoactive medication doses into a single numerical value. Despite widespread clinical use, a comprehensive synthesis of VIS as a predictor of pediatric outcomes across diverse populations is lacking. This systematic review aimed to evaluate the predictive value of VIS for mortality and morbidity in pediatric critical care populations. Methods: A systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria: pediatric population (0-18 years), explicit VIS calculation using standard formulas, reporting of clinical outcomes, and statistical analysis examining VIS-outcome relationships. Studies were excluded if limited to adult populations, case reports, conference abstracts, or editorials. Data extraction included population characteristics, VIS calculation methods, predicted outcomes, predictive performance metrics, and key findings. Results: Eighty-seven studies published between 2010-2025 met inclusion criteria, encompassing 29,920 patients across diverse settings (PICU, cardiac ICU, NICU). Post-cardiac surgery populations were most frequently studied (n=34), followed by septic shock (n=18) and neonatal populations (n=15). VIS demonstrated strong mortality prediction across populations: septic shock (AUROC 0.779-0.976), neonatal cardiac surgery (AUROC 0.83), congenital diaphragmatic hernia (AUROC 0.925), and extremely low birth weight preterm infants (AUROC 0.816-0.92). Optimal thresholds varied substantially from VIS >5 in preterm infants to >70 in myocarditis. Maximum VIS in the first 24-48 hours showed strongest associations with outcomes. VIS predicted prolonged mechanical ventilation (OR 5.20, 95% CI 3.78-7.16) and composite poor outcomes (OR 6.5-8.1). The Vasoactive-Ventilation-Renal (VVR) score outperformed VIS alone in cardiac surgery populations (AUC 0.87-0.98 versus 0.68-0.78). Discussion: VIS demonstrates consistent predictive validity across pediatric critical care populations, with performance comparable or superior to established scoring systems. Threshold heterogeneity reflects population-specific severity, age-related physiologic differences, and condition-specific considerations. Serial VIS monitoring provides incremental prognostic information beyond single measurements. Conclusion: VIS is a valid, readily calculable predictor of mortality and morbidity in pediatric critical care. Population-specific thresholds and integration with multi-organ dysfunction scores enhance predictive utility. Future research should focus on prospective validation of thresholds and implementation of VIS-guided clinical decision support.